Rising inequality of infant health in the U.S. - Emily Rauscher; David E. Rangel (Elsevier, 2020)
Has infant health inequality narrowed or grown in recent decades? Inequality may have narrowed due to expanded medical insurance coverage and greater knowledge about fetal health. However, greater income inequality may have reduced health for births to the most economically disadvantaged mothers, leading to growing infant health inequality. We use administrative birth certificate data for over 22 million births to examine trends in inequality of infant health from 1989 to 2018 in the U.S. This period allows us to consider how contextual factors - such as passage of the Affordable Care Act, changing demographics, the Great Recession, or delayed impacts of rising income inequality - may have altered infant health inequality. We assess gaps in infant health by maternal race, marital status, and education. Following previous research, we also examine gaps between the most economically advantaged mothers - married, white mothers with a college degree - and the most economically disadvantaged mothers - single, Black mothers without a high school degree. Results reveal that inequality of infant health has increased since 2010.